(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Family history is a known risk factor for breast cancer, but its prognostic value and the prognostic value of tumour characteristics in relation to family history has not been clearly established. In addition, studies of intra-familial tumour characteristics and prognosis in population-based settings are very rare. Two previous studies have suggested that breast cancer prognosis clusters within families. However, both studies lack information on HER2 expression status, which is a strong prognostic factor and could contribute to the observed results. METHODS We conducted a population-based study on 145 mother-daughter and sister-sister affected pairs using data extracted from the Geneva Cancer Registry. Histopathological characteristics were determined in archived tumour blocks by immunochemistry techniques. Breast cancer survival among family members was studied according to patient and tumour characteristics. RESULTS No significant intra-familial agreement of pathological characteristic features was observed. We found that relatives of breast cancer patients experienced a much higher risk of breast cancer death compared to the general population. However, we did not find significant concordance in good and poor breast cancer-specific survival between pairs. The small number of family pairs and deaths from breast cancer may partly explain our results. CONCLUSIONS Large-scale studies with accurate data on strong prognosticators are still needed to confirm the possibility of familial inheritance of breast cancer prognosis.